Trade Liberalization, Firm Heterogneity, and Wages : New Evidence from Matched Employer-Employee Data - Krishna, Pravin; Poole, Jennifer P.; Senses, Mine Zeynep (2012)
In this paper, the authors use a linked employer-employee database from Brazil to examine the impact of trade reform on the wages of workers employed at heterogeneous firms. The analysis of the data at the firm-level confirms earlier findings of a differential positive effect of trade liberalization on the average wages at exporting firms relative to non-exporting firms. However, this analysis of average firm-level wages is incomplete along several dimensions. First, it cannot fully account for the impact of a change in trade barriers on workforce composition especially in terms of unobservable (time-invariant) characteristics of workers (innate ability) and any additional productivity that obtains in the context of employment in the specific firm (match specific ability). Furthermore, the firm-level analysis is undertaken under the assumption that the assignment of workers to firms is random. This ignores the sorting of worker into firms and leads to a bias in estimates of the differential impact of trade on workers at exporting firms relative to non-exporting firms. Using detailed information on worker and firm characteristics to control for compositional effects and using firm-worker match specific effects to account for the endogenous mobility of workers, the authors find the differential effect of trade openness on wages in exporting firms relative to domestic firms to be insignificant. Consistent with the models of Helpman, Itskhoki, and Redding (2010) and Davidson, Matusz and Schevchenko (2008), they also find that the workforce composition improves systematically in exporting firms in terms of innate (time invariant) worker ability and in terms the quality of the worker-firm matches.